2015
DOI: 10.1080/15595692.2014.997382
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the Status Quo: Reclaiming Indigenous Knowledge through Namibia’s Postcolonial Education System

Abstract: Although Namibia has been independent for more than two decades , the school curriculum remains essentially Eurocentric despite rhetoric on educational reform. Similar to other African countries, Western ideological power continues to dominate postcolonial education, even though political power rests in the hands of African leaders. Employing George Sefa Dei's anti-colonial discursive framework, this article presents a critical analysis of postcolonial education in Namibia and of its failure to adopt a diverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…When schools developed a digital project about Indigenous narratives with parents, several parents were uncomfortable with sharing these oral stories (Hill, 2018). It might be believed that contact with the outside world played a role in acculturation and greatly affected the loss of Indigenous traditions (Matemba & Lilemba, 2015). For example, in one study, a group of families from a least-acculturated ethnic group showed less participation in school technology programs relative to all other ethnic groups who had more contact with mainstream culture (Bauchet et al, 2018).…”
Section: Barriers Concerns and Tensions In Using Technologymentioning
confidence: 99%
“…When schools developed a digital project about Indigenous narratives with parents, several parents were uncomfortable with sharing these oral stories (Hill, 2018). It might be believed that contact with the outside world played a role in acculturation and greatly affected the loss of Indigenous traditions (Matemba & Lilemba, 2015). For example, in one study, a group of families from a least-acculturated ethnic group showed less participation in school technology programs relative to all other ethnic groups who had more contact with mainstream culture (Bauchet et al, 2018).…”
Section: Barriers Concerns and Tensions In Using Technologymentioning
confidence: 99%
“…In the simplest meaning, decolonisation refers to a process by which a colonised region of a country becomes politically independent (Nakagawa, 2021). However, despite the absence of colonialism in many postcolonial states, the impacts of colonisation on lands and their peoples remain strong (Matemba & Lilemba, 2015; Nakagawa, 2021; Sianturi et al, 2022). Many Indigenous peoples live with ongoing political legacies of colonisation, dealing with structural issues of the colonial settler state.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Education systems play an important role in maintaining the legacies of colonisation. Practices in schooling that have adopted the predominance of Western knowledge over Indigenous knowledge and measured the Indigenous students' success through the colonial lens continue to marginalise many Indigenous students (Matemba & Lilemba, 2015; Sianturi et al, 2022). In addition, the negative and detrimental colonial view attached to Indigenous parents, along with the misinterpretation mentioned earlier, provokes relentless hierarchical practices of prioritising Western‐Eurocentric values in family‐school partnerships (Bang et al, 2018; Garcia, 2014).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Matemba and Lilemba (2015), traditional counting systems, including counting of livestock, apply a holistic approach that situates objects within a greater whole. As such, in the rural communities in which the student-participants grew up, counting was not inculcated as a context-free, value-neutral enterprise; instead, it involved broader social values, knowledges and practices.…”
Section: Knowledge Practices Related To Mathematicsmentioning
confidence: 99%